2004
DOI: 10.1158/0008-5472.can-03-1982
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Suppression of Epidermal Growth Factor Receptor and c-erbB-2 Reverses Aneuploidy and Malignant Phenotype of a Human Ovarian Carcinoma Cell Line

Abstract: Coexpression of epidermal growth factor receptor (EGFR) and cerbB-2 in 47-68% of ovarian cancer cells indicate their strong association with tumor formation. We examined the effects of simultaneous antisenseor immunosuppression of EGFR and c-erbB-2 expression on the invasive phenotype, aneuploidy, and genotype of cultured human ovarian carcinoma cells (NIH:OVCAR-8). We report here that suppression of both EGFR and c-erbB-2 results in regression of aneuploidy and genomic imbalances in NIH:OVCAR-8 cells, restore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Ovarian cancer cells express EGF receptor, and EGF is an autocrine growth factor for ovarian cells (54,55). We have observed the absorption of EGF and MCP-1 by ovarian tumor cells in vitro incubated with serum, 6 indicating that lower circulating levels of these molecules in ovarian cancer patients might be due to the consumption by ovarian tumor expressing specific receptors (56,57).…”
Section: Discussionmentioning
confidence: 90%
“…Ovarian cancer cells express EGF receptor, and EGF is an autocrine growth factor for ovarian cells (54,55). We have observed the absorption of EGF and MCP-1 by ovarian tumor cells in vitro incubated with serum, 6 indicating that lower circulating levels of these molecules in ovarian cancer patients might be due to the consumption by ovarian tumor expressing specific receptors (56,57).…”
Section: Discussionmentioning
confidence: 90%
“…We and others have demonstrated that gefitinib and trastuzumab have a synergistic anti-tumor effect in breast cancer cells that express both receptors. Synergism of anti-EGFR and anti-ErbB-2 agents has also been demonstrated in cells derived from tumors of different histological type, such as ovarian, non-small-cell lung and pancreatic carcinomas [28][29][30].…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, erbB2 receptor does not act in isolation. Although simultaneous suppression of EGFR and erbB2 results in a less malignant phenotype in ovarian cancer cells (Pack et al, 2004), only a minority of erbB2 altered breast cancers have co-existent overexpression of EGFR. Most metastatic breast cancers show expression for either EGFR or erbB2, and less often for both (Grupka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%